Sistem Pengarsipan Digital Di Poltekkes Kemenkes Tasikmalaya - Supriati, Eti; Ernawati; Desty Puspatriani, Annisa; Eko Setyasari, Untung; Wirasujatma, Muis (POLITEKNIK LP3I, 2025)
Digital archiving has become an essential step in enhancing efficiency and effectiveness within educational institutions, including Poltekkes Kemenkes Tasikmalaya. This study aims to identify the digital archiving strategies implemented, the challenges encountered, and the solutions applied in managing institutional records. A qualitative descriptive method was used, with data collected through observation, documentation, and interviews with administrative staff. The results indicate that the institution has begun implementing a digital archiving system, yet still faces several challenges such as limited training for human resources, inadequate digital infrastructure, and the absence of standardized operating procedures for digital archiving. Strategies adopted include internal training, the use of local cloud storage, and improvements in digital document classification. With proper strategies, the digital archiving system can function more effectively and contribute to improved administrative services.